PENGARUH PEMBERIAN PUPUK KALIUM DAN KOMPOS TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH (ALLIUM ASCALONICUM L.) VARIETAS BIMA BREBES - Ambarsari, Eriyati; Faqih, Achmad; Jaenudin , Amran (Prodi Agronomi Pascasarjana Universitas Swadaya Gunung Jati, 2023)
The purpose of the study was to determine the effect of potassium fertilizer and compost on the growth and yield of shallots of Bima Brebes variety. The research was conducted in Mekarjaya Village, Gantar District, Indramayu Regency, West Java. The time of the study was carried out from May to August 2022. The research location is located at an altitude of 493 m above sea level (asl). The type of soil associated with latosol and regosol belongs to the D (moderate) rain type. The research method used was an experimental method with a randomized block design (RBD), the treatment consisted of two factors which were repeated twice. The first factor is potassium fertilizer with four levels, namely potassium fertilizer 0 kg/ha, 50 kg/ha, 100 kg/ha, 150 kg/ha. While the second factor is compost with four levels, namely 5 tons/ha, 10 tons/ha, 15 tons/ha and 20 tons/ha. The main observation data were processed using linear model statistical tests, analysis of variance, and Scott-knot cluster further test analysis. To find out the correlation between the treatment and the growth and yield components of the shallot, the correlation used is the Product Moment Coefficient. The results showed: (1) The combination of potassium fertilizer and compost had a significant effect on plant height at 28 DAP, leaf count 28 DAP, plant growth rate (PGR) 28-35 DAP and wet tuber weight per clump, wet tuber weight per plot, tuber weight. dry weight per clump and dry tuber weight per plot. However, it had no significant effect on plant height 14 DAP, plant height 21 DAP, plant height 35 DAP, number of leaves 14 DAP, number of leaves 21 DAP, number of leaves 35 DAP, root volume, number of tillers per clump, PGR 14-21 DAP, PGR 21-28 DAP, number of tubers per clump, tuber diameter per clump. (2) The highest wet tuber weight and dry tuber weight per clump and per plot were produced by the combination of G treatment, namely 50 kg/ha of potassium fertilizer and 15 tons/ha of compost with an average dry weight of 3,645 kg equivalent to 9,125 ton/ha. (3) There was a significant correlation between plant height and number of leaves at 35 DAP with dry tuber weight per plot in the medium category. But there was no significant difference in the correlation between plant height and number of leaves aged 14 DAP, 21 DAP and 28 DAP with tuber weight per plot. Keywords: Fertilizer, Potassium, Compost, Growth, Yield, Shallot